Adding Papuan local wisdom in problem-based book: The effect on student environmental literacy - Insar Damopolii; Lissa Imbiri; Jeni Jeni; Nur Indah Ririn Fitriani Nasir; Jan Hendriek Nunaki; Nahrun Najib Siregar; Nanang Winarno (Journal of Research in Instructional, 2026)
The research aims to examine the effect of problem-based books that incorporate Papuan local wisdom on students' environmental literacy. A total of 36 students were taught using a problem-based book, which added Papuan local wisdom in the pretest and posttest research designs. They are grade VII students at a state junior high school. A total of thirty items to measure students' literacy abilities were used. The items were handed over to them to be answered twice, namely, before implementation and after the end of learning. Student responses have also been measured at the end of learning. Data were analyzed using a paired t-test. Research findings show that the value of P = 0.033 < 0.005. This finding indicates that there is an effect of using problem-based books added to Papuan local wisdom on students' environmental literacy abilities. There were 83.33% of students responding excellently and 16.67% responding well. There were no unfavorable responses from students as long as they attended the lesson. The excellent response from the students indicated that they were interested and happy to participate in learning using problem-based books, which incorporated Papuan local wisdom.